Kepastian Hukum Lelang Online (e-Auction) dalam Ekonomi Digital Tanpa Kehadiran Pejabat Lelang Kelas II - Yuliana Pratama (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The implementation of voluntary non-execution auctions that are not attended by Class II Auction Officials has the potential to cause frauds that occur in the implementation of auctions, so that there is a chance of violating auction principles. The function of Class II Auction Officials in the implementation of Voluntary Non-Execution Auctions is to lead, witness, record, and certify auction winners, all of which are further stated in the minutes of auction called auction minutes. If the organizer of the online auction does not involve auction officials, it can be doubted the validity of the implementation to the preparation of the minutes. This certainly has an impact on the authenticity of the minutes of the deed made by the Class II Auction Officer, considering that the signature of the minutes of auction is also carried out not in the presence of the official concerned. Therefore, it can be said that the evidentiary power of the auction minutes is no longer an authentic deed but rather has the evidentiary power under the hand. Keywords: Legal Certainty, e-Auction, Class II Auction Officer